Ubiquitous analysis of thyroid disorders in reproductive age group females in rural field practice area of tertiary care hospital and its correlation with body mass index - Sajid, Alina Mahewash Mohd; Suhail, Mohammed; Shafee, Mohammad; Furqan, Taha; Shaikh, Ashar; Solanke, Sachin; Rahman, Syed Inamur (International Journal of Research in Medical Sciences, 2025)
Background: Thyroid is a vital hormone producing gland that plays a major role in regulating metabolism, growth and development in the human body. It also regulates body mass index (BMI) and other metabolic functions. Methods: The present study was done on 200 females of reproductive age group in the field practice area of tertiary care hospital JIIU’s Indian institute of medical science and research, Jalna. Data collection involved general and thyroid examinations of subjects and blood sample collection for a thyroid profile. Body weight and height were also noted. Results: Thyroid disorders and their prevalence among the overall study subjects show that 79% of the population has normal thyroid function, 11% have hypothyroidism, 4.5% have hyperthyroidism, 4% have goiter, 0.5% have thyroid adenoma, 0.5% have thyroid carcinoma, and 0.5% have thyroid cyst. The Thyroid disorders in the age group 15-24, 25-34, 35-44 and 44 and older years are 8%, 5.5%, 5% and 2.5% respectively. Conclusions: Thyroid disorders are prevalent in reproductive age group females of rural Maharashtra commonest being subclinical hypothyroidism (SCH). Early diagnosis and treatment of thyroid disorders not only improve the quality of life of patients but also plays an important role in mitigating adverse maternal and fetal outcomes in the future. Further studies with larger sample sizes are needed to address the problem of thyroid disorders in rural areas.